Firm Regulation and Profit-Sharing: A Real Option Approach - Michele Moretto; Paola Valbonese (Fondazione Eni Enrico Mattei (FEEM), 2006)
To avoid high profit levels often experienced in countries where monopolies in public utility sectors are regulated through price-cap mechanisms, several regulatory agencies have recently introduced profit-sharing (PS) clauses aimed at obtaining price reductions to the benefit of consumers. However, the implementation of these PS clauses has often turned out to be severely con- trained by the incompleteness of the price-cap itself and the non-verifiability of firmsprofits. This paper studies the properties of a second-best optimal PS mechanism designed by the regulator to induce the regulated monopolist to divert part of its profits to custormers. In a dynamic model where a reg- ulated monopolist manages a long-term franchise contract and the regulator has the option to revoke the contract if there are serious welfare losses, we first derive the welfare maximising PS mechanism under verifiability of prof- its. Subsequently, we explore the sustainability of the PS mechanism under non-verifiability of profits. In a infinite-horizon game, it is showed that the dynamic sustainability of the PS clause crucially depends upon the magni- tude of the regulators revocation cost: the higher this cost, the lower the profit shared and the less frequent the regulators PS introduction. Finally, we present the endogenous and dynamic price adjustment which follows the adoption of the investigated PS mechanism in a price-cap regulation setting.
Keywords: C73; L33; L5; 330; Price-cap regulation; Profit-sharing; Real options; Anreizregulierung; Gewinn; Monopol; Franchise-Vertrag; Theorie; Realoption